The passing-on problem in damages and restitution under EU law - Strand, Magnus, 1977- (Elgar European law and practice, 2017)
'Passing-on' occurs when harm or loss incurred by a business is passed on to burden that business's customers or the next level of the supply chain. In this authoritative book Magnus Strand provides the first comprehensive examination of passing-on in EU law damages and restitution. The analysis covers a broad range of contexts including competition damages and the repayment of charges. The book offers a systematic examination of the key questions facing parties in a passing-on situation: When can downstream claimants bring an action? How can claimants demonstrate sufficient proximity to the original harmful act or unjustified transaction? Will a possibility of passing-on be relevant to the estimation of the award? These questions are assessed for actions against the EU, a Member State and private individuals. Key features of this book include: - specific EU law focus and guidance that will be relevant to lawyers throughout the EU - a multi-faceted analysis of the defence of passing-on and the position of potential claimants downstream in the supply chain - practical suggestions for consistent approaches to passing-on in EU law across existing and future contexts. This timely work will be an invaluable point of reference for practitioners working in damages and restitution law, but also in other fields of commercial law, including competition law and consumer law. Legislators and policy-makers in the EU and beyond will also benefit from the lucid analysis of the various policy choices made in the EU and US.